Beyond insulin: advancing frontiers in cell-based and genetic therapies for type 1 diabetes management - Tamer A. Addissouky (The Egyptian Journal of Internal Medicine)
Abstract Background Type 1 diabetes (T1D) is a chronic autoimmune disorder resulting in the destruction of pancreatic beta cells, leading to absolute insulin deficiency. Despite advances in exogenous insulin therapy, patients continue to face significant challenges, including glycemic variability, risk of hypoglycemia, and long-term complications. The complex interplay between genetic, immunological, and environmental factors in T1D pathogenesis underscores the need for more targeted and durable therapeutic strategies. Purpose This review aims to critically evaluate recent breakthroughs in cell-based, immunomodulatory, and gene therapy approaches for T1D, moving beyond insulin-centric management. It seeks to analyze the mechanisms, benefits, limitations, and translational potential of these emerging modalities, alongside advances in insulin formulation and delivery systems. Main body Innovations in cell-based therapies, notably stem cell-derived beta cell replacement and porcine islet xenotransplantation, are advancing toward clinical translation, supported by encapsulation technologies that enhance cell viability and immune protection. Parallel progress in immunomodulatory approaches includes both antigen-specific (oral insulin, GAD65, and proinsulin peptide therapies) and non-antigen-specific interventions (anti-CD3 monoclonal antibodies, engineered regulatory T cells). Combination immunotherapies and the advent of Teplizumab have demonstrated potential for delaying disease progression and preserving beta cell function. Gene therapy and genome editing (CRISPR/Cas9) are being refined for beta cell regeneration, protection, and immune tolerance induction, though challenges of safety, immunogenicity, and off-target effects persist. Furthermore, advances in glucose-responsive “smart” insulins, ultra-rapid-acting formulations, and automated delivery systems are optimizing glycemic control. Emerging fields such as nanotechnology, bioartificial pancreas development, and microbiome modulation further expand the T1D therapeutic landscape. Conclusion The integration of cell-based, genetic, and immunological therapies holds promise to fundamentally alter T1D management, offering prospects for long-term remission or cure. However, translational hurdles—especially immunological, ethical, and regulatory concerns—must be addressed. Multimodal, patient-tailored strategies and robust clinical validation are critical for future progress. Graphical Abstract